YOUTUBE- ASSISTED CCUI: A METHOD TO ENHANCE STUDENTS’ SOCIAL CRITICAL THINKING IN SOCIOLINGUISTIC STUDIES - Sulistyahadi; Rosiana, Caltira (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2025)
CCUI is a college learning approach designed to develop deep conceptual and critical social understanding. This approach not only improves academic achievement but also shapes analytical and critical thinking skills, preparing students to face real-world challenges. This study aims to determine the effectiveness of Critical-Conceptual Understanding Instruction (CCUI) in improving students' critical thinking skills in learning sociolinguistics. The quasi-experimental research study was conducted on English language education students who took sociolinguistics course. Data were collected using questionnaires, tests, and documentation, with parametric analysis used for data processing. Various activities were implemented to stimulate understanding, critical thinking process and learning outcomes of sociolinguistics by using YouTube as a learning tool. The results of observations, questionnaires, and tests showed that students' understanding of sociolinguistic material improved after the application of CCUI. The mean score of the pretest in the experimental class was 38.06, which increased experiment was 38.06, which increased to 82.06 in the post-test. Although some students made mistakes in answering the questions, their overall understanding showed a significant improvement. Students' social critical thinking skills were evident from their responses and ideas during the learning process, as well as from the comparison between pretest and post-test scores. Based on the analysis of the test results of learning outcomes, learning completeness, student activities, and critical thinking development, CCUI in sociolinguistic learning using YouTube effectively improves students' critical thinking skills.